Our little secret [large type] - Jackson, Lisa (Center Point Large Print, 2024)
"Brooke Harmon is ready to end her brief affair. Gideon Ross is charming and sexy, but he's not worth throwing away everything she holds dear. So she breaks it off, hoping Gideon will understand. He doesn't. Gideon insists that he and Brooke are meant to be together. Finally, he backs off, but not before issuing a promise: he'll never let her go. Little more than a year later, Brooke wants to believe it's all behind her. Her family has survived intact. Gideon has vanished. But the fear hasn't disappeared. Brooke can't tell how much of it is paranoia, and how much is justified, but she's worried. And maybe she's right to be. Because Gideon is a man who keeps his promises . . ."--